Botanical and nutritional composition of maize stover, intakes and feed selection by dairy cattle - Methu, J.N.; Owen, E.; Abate, A.L.; Tannen, J.C. (Elsevier, 2001)
Maize stover is the most abundant crop residue in the central Kenya highlands and it is often the sole forage offered to dairy cattle during the dry seasons. In recent years increasing offer rates of crop residues (excess feeding) to promote selective feeding by confined animals has been shown to improve utilization of the residues, but no studies have been conducted with dairy animals offered maize stover. This study was conducted to determine the effects of increasing the ad libitum amounts of maize stover offered, on intake, selection and milk production by dairy cattle, when supplemented with cottonseed cake. The effects of post harvest handling on the quality of maize stover were also studied Hybrid 511 maize was grown under similar agronomic conditions in 2 consecutive years, 1994 and 1995. Maize harvested under dry weather conditions in 1994 produced stover with a higher leaf + sheath + husk:stem ratio (1.48), than maize harvested in 1995 under rainy weather conditions (0.99). In both years, leaves recorded the highest crude protein (CP) contents among the botanical components. Acid detergent lignin (ADL) levels were highest in stem (85 g/kg DM) and lowest in husk (29 g/kg DM). Stem had the lowest digestible organic matter (DOMD) values (405 g/kg DM) while husk had the highest (707 g/kg DM). Stover intake by dairy cows increased significantly from 19 to 26 and then to 30 g DM/kg live weight per day, as the amount of stover offered increased from 31 to 59 and then to 86 g DM/kg live weight per day, respectively. The cows selected for more leaves and husks as the amount of stover offered increased. All animals were supplemented with 3.2 kg DM/day of cottonseed cake. Milk yields increased significantly (P < 0.05) from 10.0 to 11.2 and then to 12.2 kg/cow/day. It was concluded that offering excess can be an effective strategy to improve the intake of maize stover and increase milk production although adoption of the technology would depend on other factors such as availability of large amounts of stover and an economical use of the refusals.